The role of transport and traffic in national economy - Horst Heldmann (Intereconomics, 1973)
This article deals with transport as a service and as an investment sector. It shows the special role of transport in national economy and draws attention to some problems, which are characteristic and of particular importance to LDCs.
Keywords: 330; Traffic Policy